2010
DOI: 10.1371/journal.pntd.0000794
|View full text |Cite
|
Sign up to set email alerts
|

A Screening Pipeline for Antiparasitic Agents Targeting Cryptosporidium Inosine Monophosphate Dehydrogenase

Abstract: BackgroundThe protozoan parasite Cryptosporidium parvum is responsible for significant disease burden among children in developing countries. In addition Cryptosporidiosis can result in chronic and life-threatening enteritis in AIDS patients, and the currently available drugs lack efficacy in treating these severe conditions. The discovery and development of novel anti-cryptosporidial therapeutics has been hampered by the poor experimental tractability of this pathogen. While the genome sequencing effort has i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 61 publications
1
70
0
Order By: Relevance
“…Cryptosporidium drug discovery has been hampered by lack of an in vitro culture system that can continuously culture the parasite and the lack of genetic tools to construct transgenic reporter parasites that would greatly facilitate screening efforts (Sharling et al, 2010). Recent developments in the in vitro cultivation have revealed that Cryptosporidium can complete its life cycle in media devoid of host cells (Aldeyarbi and Karanis, 2014;Boxell et al, 2008;Hijjawi et al, 2004Hijjawi et al, , 2010Kartashev et al, 2009) and both cell and cell-free cultures have demonstrated that Cryptosporidium may not be an obligate intracellular parasite and can in fact multiply extracellularly (Borowski et al, 2010;Hijjawi et al, 2002;Huang et al, 2014;Karanis et al, 2008;Koh et al, 2013;Rosales et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cryptosporidium drug discovery has been hampered by lack of an in vitro culture system that can continuously culture the parasite and the lack of genetic tools to construct transgenic reporter parasites that would greatly facilitate screening efforts (Sharling et al, 2010). Recent developments in the in vitro cultivation have revealed that Cryptosporidium can complete its life cycle in media devoid of host cells (Aldeyarbi and Karanis, 2014;Boxell et al, 2008;Hijjawi et al, 2004Hijjawi et al, , 2010Kartashev et al, 2009) and both cell and cell-free cultures have demonstrated that Cryptosporidium may not be an obligate intracellular parasite and can in fact multiply extracellularly (Borowski et al, 2010;Hijjawi et al, 2002;Huang et al, 2014;Karanis et al, 2008;Koh et al, 2013;Rosales et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One compound, P131, was designed to be retained in the gastrointestinal tract and therefore exceeded the recommended TPSA (TPSA of Յ140 Å 2 ). Compounds were evaluated for enzyme inhibition and antiparasitic activity against a reporter Toxoplasma gondii strain (T. gondii/ CpIMPDH) engineered to rely on CpIMPDH for the production of guanine nucleotides (54). Compounds that performed well in these two assays, with 50% inhibitory concentrations (IC 50 ) of Յ20 nM and EC 50 s of Յ2 M, were candidates for testing in the IL-12 knockout mouse model of acute cryptosporidiosis.…”
Section: Resultsmentioning
confidence: 99%
“…The excystation mixture was diluted with Ultraculture medium (BioWhittaker Inc., Walkersville, MD), and approximately 1 ϫ 10 5 oocysts and sporozoites were allowed to infect confluent human ileocecal adenocarcinoma epithelial cells (HCT-8) or Madin-Darby canine kidney cells (MDCK). The monolayer was washed with PBS after 3 h and incubated with fresh Ultraculture medium with or without test compounds, inhibitor and media were refreshed after 24 h, and the parasites were cultured for a total of 48 h. Cultures were fixed and counted using an anti-C. parvum fluoresceinlabeled monoclonal antibody (C3C3-fluorescein isothiocyanate [FITC]) or a high-content imaging assay (54). The 50% effective concentration (EC 50 ) values were calculated using the Hill-Slope model using Prism v5 (GraphPad Software Inc., La Jolla, CA): % growth ϭ (maximum Ϫ minimum)/{1 ϩ (EC 50 …”
Section: Methodsmentioning
confidence: 99%
“…Thus, the exclusive reliance on the salvage pathway by Cryptosporidium and its high metabolic demand for nucleotides due to the parasite's complicated lifecycle make IMPDH a potential drug target candidate. This hypothesis is supported by the recent discovery of several Cryptosporidium IMPDH inhibitors Johnson et al, 2013;Maurya et al, 2009;Sharling et al, 2010;Umejiego et al, 2008).…”
Section: Introductionmentioning
confidence: 80%
“…Despite this, efforts to develop new and more effective treatments for this disease have been hindered by (1) lack of suitable targets and (2) lack of target validation and transfection tools. The completion of the Cryptosporidium genome (Abrahamsen et al, 2004;Xu et al, 2004), which resulted in a range of potential drug targets being identified, has overcome the first hindrance and IMPDH is now a well recognised and important drug target Johnson et al, 2013;Maurya et al, 2009;Sharling et al, 2010;Umejiego et al, 2008).…”
Section: Discussionmentioning
confidence: 99%